Effective Properties of Micropolar Laminated Media Under the Influence of Constitutive Property Rotation - Espinosa-Almeyda, Yoanh (Springer, 2024)
The two-scale asymptotic homogenization method (AHM) is implemented to determine the effective behavior of periodic laminated micropolar elastic composites under perfect contact conditions. The rotation effect of constitutive property on the effective behavior of the composite is also analyzed. From AHM, the main results for centro-symmetric micropolar elastic composites are reported, including the statement of the local problems and the analytical expressions for the effective stiffness and torque properties. In particular, periodic bi-laminated composites are examined. In these composites, one constituent (referred to as layer A) has cubic symmetry with the principal axis of symmetry y3 and the other constituent is defined with properties that result from a rotation θ of the material properties of layer A in the y1y2-plane with respect to y3-axis. Numerical results are presented and validated. As a result, the effective behavior of the micropolar elastic composite is characterized by the quantity of independent effective moduli.